2016
DOI: 10.1002/admi.201600580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conformality and Crystallinity for Ultrathin 4 nm Compact TiO2 Layers in Perovskite Solar Cells

Abstract: The rapid rise in power conversion efficiencies of lead-based perovskite solar cells (PSCs) has established their promise, motivating scale-up and commercialization. As a thin film solar cell, interfacial properties are key to the performance of PSCs; there is a need to further understand which properties are critical to control. In this work, the impact of the compact TiO 2 (com-TiO 2 ) film properties on the performance of mesoporous PSCs is studied. Com-TiO 2 layers are fabricated by spray pyrolysis as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…It was already demonstrated on photocurrent, XPS and other investigations in the previous literature that ALD TiO 2 nanolayers are of very high quality compared to other TiO 2 nanostructures [33,40,41].…”
Section: Resultsmentioning
confidence: 87%
“…It was already demonstrated on photocurrent, XPS and other investigations in the previous literature that ALD TiO 2 nanolayers are of very high quality compared to other TiO 2 nanostructures [33,40,41].…”
Section: Resultsmentioning
confidence: 87%
“…The SnO 2 film morphology is expected to significantly affect the PSC performance because planar PSCs have a direct interface between the ETL and the perovskite layer. The improved conformality could result in good contact that affords enhanced electron transport [ 25 ]. The SEM images of perovskite layer fabricated from varied ETLs were provided in supporting information (SI) Additional file 1 : Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the highly dense TiO 2 layer was observed to have a positive impact on effectively blocking the migration of holes in perovskite under an indoor light environment and preventing direct contact between the perovskite layer and the electrode, which resulted in a higher efficiency. [ 77 ] Different methods were investigated for TiO 2 film preparation, such as low‐temperature atomic layer deposition (LT‐ALD), [ 78 ] application of high‐temperature sol–gel (SG) coatings, [ 79 ] and deposition through high‐temperature spray pyrolysis (SP). [ 80 ] Di Giacomo et al utilized these three methods to explore the influence of film preparation methods on the performance of perovskite‐based indoor photovoltaics [11f] .…”
Section: Advances In Indoor Photovoltaicsmentioning
confidence: 99%
“…Consequently, higher PCEs were achieved in the ALD-based cells (an average PCE of 20.9%) when compared with the other two types of devices (an average PCE of 0.1% and 4.8% for the SP-and SG-based cells, respectively) under 200 lx. This occurrence was because the compact TiO 2 created by ALD had a smaller pinhole density, [64,78,81] which prevented the recombination between the perovskite layer and the transparent conducting oxide. Moreover, the SEM image showed that the LT-ALD TiO 2 induced a small crystal overlay on top of the perovskite film, thereby preventing direct contact between the TiO 2 and the hole translate materials (Spiro-OMeTAD), thereby reducing the additional recombination pathways.…”
Section: Modified Layermentioning
confidence: 99%